Enabling sustainable agrifood value chain transformation in developing countries - Hidayati DR; Garnevska E; Childerhouse P (Elsevier Ltd, 2023)
As agri-food value chains in developing countries transform to serve higher value markets, they are coming increasing under pressure to embrace sustainable practices. Many key players, particularly smallholders, find it difficult to comply with sustainable practice requirements. They face various barriers in the chain's operation (in terms of governance and value addition), while their primary focus is on increasing incomes to alleviate poverty. Therefore, this study empirically identifies and analyses the factors that enable sustainable value chain transformation in developing countries. A total of three key dimensions (sustainability, governance, and value addition) were used to explore the factors that enable sustainable value chain transformation. Furthermore, the existing practice as well as future intentions towards sustainable value chain practices are evaluated. A quantitative method was employed within Indonesia's cashew sector, and structured interviews were conducted with 159 smallholders from the key production area on Madura Island. The analysis was performed using a combination of descriptive and principal component analyses (PCA). A total of eight factors that enable sustainable transformation were identified. Farm practices and information communication were identified as the most significant enabling factors, as well as stakeholder support, certification motivation, and market expansion. Conversely, the most challenging factors were pre-harvesting value, value capturing, and value adding activities. The results reveal the current practices, barriers, and enablers, and provide policy and practice insights for transforming sustainable value chains in developing countries.
Keywords: Enablers and barriers; Sustainable value chains; Transformation; Smallholders; Agrifood; Developing countries